Dissemination a model of farmer-to-farmer learning process (FFLP) and its technologies to local administration organizations for improving the agricultural extension service - Krailert Taweekul (2018)
© 2015 American Scientific Publishers, All rights Reserved. The purpose of this paper is (1) to convey the farmer-to-farmer learning process model to local administration organization and (2) to apply the FFLP model in improving the agricultural extension service of local government and scaling out. Interview on focus group with local government staff was used to collect data. The study found that majority of TAOs officers, about approximately 76% learnt the FFLP model through introduced technologies in which farmers implemented in the villages: Custard Apple (CA), Organic Fertilizer (OF), Herbal Repellent Extraction (HE) and Cassava for Animal Feed (CF). TAO staff mentioned that most benefits farmer gained from FFLP were income increase and cost reduction. Five steps of FFLP model have been used to investigate scaling out in other areas: (1) initiation, (2) farmer information (3) technology adaptation, (4) assessment and (5) sharing results.